1998
DOI: 10.1073/pnas.95.3.1142
|View full text |Cite
|
Sign up to set email alerts
|

Marrow stromal cells as a source of progenitor cells for nonhematopoietic tissues in transgenic mice with a phenotype of osteogenesis imperfecta

Abstract: Marrow stromal cells from wild-type mice were infused into transgenic mice that had a phenotype of fragile bones resembling osteogenesis imperfecta because they expressed a human minigene for type I collagen. In mice that were irradiated with potentially lethal levels (700 cGy) or sublethal levels (350 cGy), DNA from the donor marrow stromal cells was detected consistently in marrow, bone, cartilage, and lung either 1 or 2.5 mo after the infusions. The DNA also was detected but less frequently in the spleen, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
332
0
7

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 507 publications
(348 citation statements)
references
References 41 publications
8
332
0
7
Order By: Relevance
“…At 2 1 2 months after cell infusion, 4-19% of the cells in various tissues including the bones of the recipient mice were reported to be of donor origin. 38 Several other investigators have reported similar findings in murine, sheep and baboon animal models. [39][40][41][42] Using similar approaches as above but with bettercharacterized mouse bone marrow stromal cells, the current authors have shown that cells infused into mouse femurs persist in bone.…”
Section: Cell Therapysupporting
confidence: 52%
See 1 more Smart Citation
“…At 2 1 2 months after cell infusion, 4-19% of the cells in various tissues including the bones of the recipient mice were reported to be of donor origin. 38 Several other investigators have reported similar findings in murine, sheep and baboon animal models. [39][40][41][42] Using similar approaches as above but with bettercharacterized mouse bone marrow stromal cells, the current authors have shown that cells infused into mouse femurs persist in bone.…”
Section: Cell Therapysupporting
confidence: 52%
“…Previous studies in mice and humans have demonstrated that bone marrow-derived mesenchymal stem cells will migrate to bone when administered systemically. [37][38][39]46 We previously showed that direct injection of the cells into the mouse bone marrow cavity leads to a wide distribution of the cells in different tissues of the host. 39 Since early treatment for OI will be essential, mesenchymal stem cells transduced with therapeutic genes will need to be delivered early during development.…”
Section: Ex Vivo Gene Delivery To Bonementioning
confidence: 99%
“…The common features among the cells referred to by different investigators as MSCs is that they grow as adherent cells in culture and have the capacity to differentiate into osteoblasts, chondroblasts and adipocytes when exposed to the appropriate stimuli in vivo and in vitro. [5][6][7][8][9] Transplantation of whole bone marrow including MSCs, and hematopoietic stem cells has been used in clinical trials to treat osteogenesis imperfecta, a genetic disease affecting the bones of affected children. 10 In three of three children transplanted with normal bone marrow cells including mesenchymal stem cells from allogeneic matched siblings, there was a significant decrease in the number of fractures in the first 6 months following the transplant.…”
Section: Stromal Cellsmentioning
confidence: 99%
“…Initial attempts to test this strategy for OI were carried out in transgenic mice that developed brittle bones because they expressed an internally deleted minigene of human COL1A1. 3 The mice were infused with wild-type adult stem cells referred to as mesenchymal stem cells or marrow stromal cells (MSCs) as a source of osteoprogenitors. Infusions of the MSCs produced small but significant increases in both the collagen and mineral content of bone.…”
Section: Introductionmentioning
confidence: 99%
“…Infusions of the MSCs produced small but significant increases in both the collagen and mineral content of bone. 3 Subsequently, a two-stage clinical trial was initiated for the use of MSCs in patients with severe OI. [4][5][6] In the first stage, the patients underwent marrow ablation followed by a bone marrow transplant from HLAcompatible normal siblings.…”
Section: Introductionmentioning
confidence: 99%